Downregulation of miRNA-1-3p modulates cyclic stretch-mediated proliferation of vascular smooth muscle cells through regulation of ETS-1 - Wang, Xizhen; Li, Aihua; Duan, Ruikang; Zhang, Bin (Archives of Biological Sciences, 2020)
Paper description: Mechanical stretch modulates the proliferation of vascular smooth muscle cells (VSMCs) which plays an important role in hypertension pathogenesis. The role of miRNA-1-3p which is downregulated in the aorta of the spontaneous hypertension rat (SHR), on the proliferation of VSMCs induced by mechanical cyclic stretch was investigated. MiRNA-1-3p regulates VSMC functioning through regulation of ETS-1 during hypertension-induced vascular remodeling. Dual luciferase reporter assays revealed that V-ets erythroblastosis virus E26 oncogene homolog 1 (ETS-1) is the direct target of miRNA-1-3p. MiRNA-1-3p may be a viable therapeutic target for hypertension. Abstract: Mechanical stretch modulates the proliferation of vascular smooth muscle cells (VSMCs) and plays an important role in the pathogenesis of hypertension, but the underlying mechanisms are unclear. We investigated the role of microRNA-1-3p (miRNA-1-3p) on the proliferation of VSMCs induced by mechanical cyclic stretch. Our data show that miRNA-1-3p is downregulated in the aorta of the spontaneous hypertension rat (SHR). Pathological mechanical stretch at 15% suppressed the expression of miRNA-1-3p, calponin and SM22, but enhanced the proliferation of VSMCs as well as the expression of the V-ets erythroblastosis virus E26 oncogene homolog 1 (ETS-1), collagen type I alpha (Col-1a), collagen type III alpha (Col-3a) and elastin. Overexpression of miRNA-1-3p inhibited cell proliferation and induced the expression of calponin and SM22, but decreased the expression of ETS-1, Col-1a, Col-3a and elastin. Mechanical stretch at 15% combined with losartan treatment increased the expression of miRNA-1-3p, calponin and SM22, and decreased the expression of ETS-1, Col-1a and Col-3a. Dual luciferase reporter assays revealed ETS-1 as a direct target of miRNA-1-3p. These findings suggest that miRNA-1-3p regulates VSMC function through ETS-1 regulation during hypertension-induced vascular remodeling. MiRNA-1-3p may be a viable therapeutic target for hypertension.